The macroeconomic aspects of sport in Europe: a cross-country comparison - Mamcarczyk, Mariola; Szyszko, Magdalena (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
In this paper we aim to investigate the importance of the sports sector of the economy for macrolevel performance in the European Union Member States. The problem that we address is worthy of research focus as sport is a dynamically expanding and important sector of the economy. The increasing importance of sport in national economies cannot be fully analysed due to the lack of sufficient statistical data. In this paper, we provide a comparison of the Eurostat sports collections results and Sport Satellite Account-based examination of the contribution of sport to the GDP and value added. The analysis of statistical data is preceded by a description of the sports sector measurement. We establish that the contribution of sport is more remarkable for developed economies, however it has also been increasing over time in other EU Member States. This can be observed for employment, changes in enterprises’ statistics, and international trade. Household spending on sports goods and services also increases even if the Great Recession led to a downturn in sport consumption in some countries. The frequency and coherence of sports data collections related to its economic significance is not satisfactory. The issue needs to be given a higher priority by public authorities.